Total annulus excision tympanoplasty – a solution to recurrent myringitis: double blind randomised trial. Issue 3 (27th March 2022) - Verma, N; Singhal, P; Prabhu, K P Surendra; Sehra, R; Yadav, R; Aeron, B Singh; Munjal, S; Hussain, A; Agarwal, S; Sharma, M Prakash
Abstract: Objective: In spite of continuous refinements in tympanoplasty techniques, results are variable, and it is not uncommon to see a discharging eardrum even after a good graft uptake. This study aimed to evaluate the efficacy of total annulus excision tympanoplasty in comparison with conventional underlay tympanoplasty. Method: This was a double blinded, randomised, controlled trial performed at a tertiary care centre. After inclusion and exclusion criteria were met, 56 patients were enrolled and randomised, and 28 patients were allocated to each group (group A (conventional tympanoplasty) and group B (total annulus excision)). Patients and evaluators were blind to the procedure performed. Results: Patients in group B (total annulus excision) showed better graft uptake and no discharge with better gains in air conduction thresholds ( p < 0.05) when compared with group A (conventional tympanoplasty). Conclusion: In view of the advantages it offers, total annulus excision tympanoplasty may be preferred over the conventional techniques in patients with central perforations.